Therapeutic perspective of COVID-19 against corticosteroids - Lima, Mercia Mendes de; Rodrigues, William Augustine; Vasconcelos, John Peter; Araújo, Igor Gomes de; Morais, Arlandia Cristina Lima Nobre de (Seven Editora, 2023)
Coronaviruses belong to a broad family called Coronoviridae, they are simple RNA viruses. In SARS-CoV-2 infection, a cytokine storm occurs in the body, responsible for tissue damage, and pulmonary and systemic inflammation. For this reason, corticosteroids appear as a viable option. This study conducted a systematic review of the pharmacotherapy of steroidal anti-inflammatory drugs used in hospitalized patients with COVID-19. The study was conducted in January 2023, using the SCIELO and PUBMED databases. The keywords were: corticosteroid, SARS-CoV-2, therapy, corticosteroids, hospitalized, and COVID-19 combined with the Boolean operators AND and OR. Articles published from 2020 to 2022 in the languages Portuguese and English were included. Of the 8 articles included in this review, 50% (n=4) are cohort studies, 37.5% (n=3) are clinical studies, and 12.5% (n=1) are observational studies. As for the year of publication, 25% (n=2) are from 2020, 62.5% (n=5) are from 2021 and 12.5% (n=1) are from 2022. Of the country where the survey was conducted, 37.5% (n=3) were conducted in Iran. China, South Africa, Spain, Colombia, and Lisbon had 12.5% (n=1) of studies each. The population samples visualized in the 8 studies ranged from 62 patients to 774 patients, with a mean age ranging from 53.5 to 64 years, 55.8% men, and 44.1% women. Among the comorbidities observed in each study, Diabetes Mellitus and hypertension were the most common, followed by cardiovascular events, Chronic Obstructive Pulmonary Disease, dyslipidemia, and obesity or HIV. Regarding the severity of COVID-19, 50% (n=4) of the studies were done with patients who had the severe form of the disease, 37.5% (n=3) moderate to severe, and 12.5% (n=1) of the studies reported that 63.6% of the sample (49/77) evolved to the severe form of the disease. Among the corticosteroids included in the studies, those that presented the best clinical outcomes were methylprednisolone in 50% (n=4) of the studies with doses ranging from 80mg/day to 500mg/day during the range of 3 to 14 days of treatment. Prednisolone was followed in 12.5% (n=1) of the studies at a dose of 25mg/day for 5 days of treatment and dexamethasone in 25% (n=2) of the studies. The therapeutic benefit of corticosteroids for the control of moderate and severe cases caused by the so-called "cytokine storm" that occurred in the body of human beings infected by SARS-CoV-2 is evident. DOI:https://doi.org/ 10.56238/devopinterscie-217